2020
DOI: 10.3390/ai1010005
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Anomalies in Large-Scale Cyberattacks Using Fuzzy Neural Networks

Abstract: The fuzzy neural networks are hybrid structures that can act in several contexts of the pattern classification, including the detection of failures and anomalous behaviors. This paper discusses the use of an artificial intelligence model based on the association between fuzzy logic and training of artificial neural networks to recognize anomalies in transactions involved in the context of computer networks and cyberattacks. In addition to verifying the accuracy of the model, fuzzy rules were obtained through k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 117 publications
(128 reference statements)
0
6
0
Order By: Relevance
“…Some forecasting methods, such as autoregressive integrated moving average (ARIMA), rely on historical data to produce predictions. However, these tactics are inefective if the data lack discernible patterns and exhibit high levels of random volatility [62,63]. Machine learning and deep learning algorithms are much more efcient and dependable than earlier approaches.…”
Section: Identifying Patterns and Anomaliesmentioning
confidence: 99%
“…Some forecasting methods, such as autoregressive integrated moving average (ARIMA), rely on historical data to produce predictions. However, these tactics are inefective if the data lack discernible patterns and exhibit high levels of random volatility [62,63]. Machine learning and deep learning algorithms are much more efcient and dependable than earlier approaches.…”
Section: Identifying Patterns and Anomaliesmentioning
confidence: 99%
“…Izakian et al [50] proposed to introduce fuzzy in anomaly detection by proposing a fuzzy c-means-based technique. Souza et al [53] presented a fuzzy neural network-based approach for detecting anomalies in massive cyberattacks. In [54], the authors presented an effective clustering-based realtime anomaly detection system.…”
Section: Related Workmentioning
confidence: 99%
“…In [50][51][52], the authors offered fuzzybased approaches for real-time anomaly detection. In [53], the authors suggested a fuzzy neural network approach with the goal of identifying anomalies in significant cyberattacks. An effective real-time clustering-based anomaly detection system was described by the authors in [54].…”
Section: Introduction 1origin Of the Problemmentioning
confidence: 99%
“…In [33], the authors proposed a real-time eGFC, to the log-based anomaly detection problem with time-varying data from the Tier-1 Bologna computer center. In [34], the authors have discussed a model using the association between fuzzy logic and ANN to recognize anomalies in transactions involved in the context of computer networks and cyberattacks. A sequential k-means clustering algorithm which updates cluster-center with the new arrival of each data instance is proposed in [23].…”
Section: Related Workmentioning
confidence: 99%